VA Facility Upgrades Continuity of Mental Health Care - Buckley, Rita (MD Conference Express, 2015)
The beneficial effects of postdischarge follow-up after inpatient hospitalizations have been documented, as has increased recidivism from lack of such care after discharge. Using this literature for evidence-based research, this article discusses a system-wide postdischarge initiative at the Veterans Affairs New York Harbor Healthcare System to improve con-tinuity of care.